Effects of Environmental Factors, Ages and Breeds on Semen Characteristics in Thai Indigenous Chickens: A One-year Study - Sonseeda, Pornjit; Vongpralub, Thevin; Laopaiboon, Banyat (The Thai Journal of Veterinary Medicine, 2013)
Several reports on the semen characteristics of domestic fowl have indicated that environmental factors, breed and age significantly affect semen quality. There is, however, a paucity of data on effects of environmental factor, breed and age on semen characteristic in Thai indigenous chickens. The aims of the present study were to investigate the effects of annual ambient temperature and humidity, local breeds (i.e. Lueng hang kaow, Pradoo hang dam and Chee), and ages (10 and 18 months) on sperm production and semen quality among Thai native cocks. Thirty-six Thai native cocks were housed under natural environmental conditions, and semen was collected routinely twice a week using the massage method. Sperm production and semen quality were determined every two weeks for one year. Semen was evaluated for volume, mass movement, % total motility, % live normal, sperm concentration/ml and sperm number/ejaculate. Over the 12-month period, ambient temperature and humidity did not significantly affect sperm production and semen quality (p < 0.05). Breeds and ages also had no effect on semen characteristics among the Thai native cocks. The result of the present study indicates that the sperm production and semen quality of captive Thai native cocks were not influenced by environmental factors, breeds and ages.